Specjalne i nie-specjalne. Dylematy współczesnego podejścia do potrzeb osób z niepełnosprawnością - Podgórska-Jachnik, Dorota (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The article is devoted to the problems of disability seen through the prism of needs, both those referred to as special (special educational, developmental, professional needs), as well as those universal. The term (special) needs were analyzed, in particular the problem of losing its basic, psychological significance in the special pedagogy of recent years, as well as its theoretical and practical explorations in relation to nursing-compensating, educational and therapeutic activities. Text points attention to the need to update analyzes consistent with the idea of inclusion, in relation to the issue of the needs of people with disabilities, as a motivating factor and compensation area.